The impact of tourism demand, government expenditure on education and income on the environment in ASEAN-5 countries - Nur Fadzlunnisaa Wakimin,; A.A. Azlina,; Hazman Samsudin,; Mahirah Kamaludin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
ASEAN countries heavily rely on tourism and therefore are vulnerable towards environmental disruptions. Tourism demand (TD), government expenditure on education (GEE) and income (INC) are among the main factors that increase the total global carbon dioxide emissions which lead to climate change, hence making them the key focus areas in ASEAN-5 countries. This study analysed whether the environmental Kuznets curve (EKC) holds for all ASEAN countries from 1970 until 2014 using nonlinear autoregression distribution lag (NARDL) method. It also analyses whether all variables are asymmetric to the environment in the long-run. In the long-run, the carbon dioxide emission response could have a negative change in INC for Malaysia (MLY), India (IND), Singapore (SNG), and the Philippines (PHL). However, in Thailand (THL), the carbon dioxide emission response could lead to a positive change in INC. This study found an asymmetric long-run effect of the INC, GEE, and TD on the environment in ASEAN-5 countries. In conclusion, EKC does not hold in all cases, but is detected in some of the variables. In this case, legal regulations are needed to avoid environmental degradation due to inefficient economic mechanisms that are insufficient to reduce the total global carbon dioxide emissions.